PROFIL KANDUNGAN METABOLIT SEKUNDER TUMBUHAN OBAT BIOPHYTUM PETERSIANUUM DAN BIOPHYTUMSENSITIVUM - Sukarsono . (Jurnal Gamma, 2010)
The research objective is to obtain information of the metabolic profile setandar petersianauunBiophytum medicinal plants, to analyze the content of active ingredients contained in Biophytumpetersianum and B sensitivum. Analisisi active ingredient will be conducted in two stages. The firststage of screening performed to identify the type of active ingredient (secondary metabolites) thatare common in both types of plants. The analysis is performed to determine the presence of theflavonoid, phenolic, saponins, steroids, terpenoids and alkaloids. Step-by-step research work doneat the first stage performed as Method Culvenor Fitzgerald (in Djaswir Dervish, 2006).Biophytum petersianum and Biophytum sensitivum secondary metabolites containing compounds:flavonoids, phenolic and alkaloid, fitohormon well contained by Biophytum petersianum and Biophytumsensitivum expected to be a compound daidzein (read; Deidzein). Plants thus Biophytum petersianumand B sensitivum can be used as a source of natural phytoestrogens